IPO AFTERMARKET LIQUIDITY DURING THE DARK TIME - Revina Wigantini, Ghea
COVID-19 pandemic has become one unexpected period on earth. This pandemic leads to shakes in many aspects, including the stock market. This study calls this pandemic as the dark time. As this dark time also hit the market significantly, this study wonders if some firms are confident enough to do Initial Public Offering (IPO). This study investigates the effect of the COVID-19 pandemic, proxy with the fear index on IPO aftermarket liquidity in ASEAN. Using panel regression analysis for two proxies of IPO aftermarket liquidity, volume and turnover, this study exercises the data of 90 IPO companies in the ASEAN region over four periods after their IPOs. Moreover, this study also provides the result in the samples as respective countries and as the ASEAN region. The results prove that the COVID-19 fear index significantly affects liquidity for all proxies, in Indonesia, Malaysia and Thailand but not in Singapore and the Philippines. As the region, the fear index has negative influence on the liquidity, both for 30-, 60-, 90- and 100days horizons. The greater liquidity of an IPO company depends on the decrease of